2023
DOI: 10.3233/jifs-223093
|View full text |Cite
|
Sign up to set email alerts
|

BOSF-SVM: A thermal image-based fault diagnosis method of circuit boards

Abstract: In recent years, the lack of thermal images and the difficulty of thermal feature extraction have led to low accuracy and efficiency in the fault diagnosis of circuit boards using thermal images. To address the problem, this paper presents a simple and efficient intelligent fault diagnosis method combined with computer vision, namely the bag-of-SURF-features support vector machine (BOSF-SVM). Firstly, an improved BOF feature extraction based on SURF is proposed. The preliminary fault features of the abnormally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…They found that AlexNet and MobileNet had the best performance on different metrics. In [55] the Bag-of-Features model(BOF) was integrated with the SURF technique to come up with a Bag-of-SURF-Features (BOSF) vector for each image. They used these features in a SVM for classification of two types of circuit board images, into faults that lead to hotspots in circuit boards.…”
Section: Related Workmentioning
confidence: 99%
“…They found that AlexNet and MobileNet had the best performance on different metrics. In [55] the Bag-of-Features model(BOF) was integrated with the SURF technique to come up with a Bag-of-SURF-Features (BOSF) vector for each image. They used these features in a SVM for classification of two types of circuit board images, into faults that lead to hotspots in circuit boards.…”
Section: Related Workmentioning
confidence: 99%